Genomic epidemiology and multilevel genome typing of Bordetella pertussis - Michael Payne; Zheng Xu; Dalong Hu; Sandeep Kaur; Sophie Octavia; Vitali Sintchenko; Ruiting Lan (Emerging Microbes and Infections, 2023)
Bordetella pertussis causes pertussis (or whooping cough), a severe respiratory infectious disease in infants, although it can be prevented by whole cell and acellular vaccines. The recent pertussis resurgence in industrialised countries is partly attributed to pathogen adaptation to vaccines, while emergence of antimicrobial resistance, specifically to macrolides in China, has become a concern. Surveillance of current circulating and emerging strains is therefore vital to understand the risks they pose to public health. Although the use of genomics-based typing is increasing a genomic nomenclature for this pathogen has not been well established. Here, we implemented the multilevel genome typing (MGT) system for B. pertussis with five levels of resolution, which provide targeted typing of relevant lineages and discrimination of closely related strains at the finest scale. The lower resolution levels (MGT2 and MGT3) describe the distribution of major vaccine antigen alleles including ptxP, fim3, fhaB and prn, as well as temporal and spatial trends within the B. pertussis global population. Mid-resolution levels (MGT3 and MGT4) enable typing of antibiotic-resistant lineages and Prn deficient lineages within the ptxP3 clade. The high-resolution level (MGT5) can capture finer-scale epidemiology such as outbreaks and local transmission events, with comparable resolution to existing genomic methods of strain-relatedness assessment. The scheme offers stable MGT-type assignments aiding harmonisation of typing and communication between laboratories. The scheme is available at https://mgtdb.unsw.edu.au/pertussis, is regularly updated from global data repositories and accepts public submissions. The MGT scheme provides a comprehensive, robust, and scalable system for global surveillance of B. pertussis.